Mathematical model for the available phosphorus, phytoplankton and zooplankton in the Lake Ohrid - Mitreski, Kosta; Koneski, Z; Davchev, Dancho; Naumoski, T (WIT Press, 1998)
In the paper by Mitreski et al.' a dynamic biogeochemical model has been proposed, which tends to describe some of the processes that contribute to the eutrophication of Lake Ohrid. By balancing the complexity between the scope of the model and the available data, we selected state variables and formulated mathematical expressions. With three differential equations, we took into account the change of available phosphorus, as well as time dependent behaviour of phytoplankton and zooplankton concentrations in the lake. By considering both model output and lake-wide observations, the suitability of the model was analysed. The main goal of this paper is to give experimental validation of the proposed mathematical model. Four groups of phytoplankton and seven zooplankton types were considered in the analysis. The simulated results from the model are validated with the measured values from the lake. We concluded that the model shows the general trends and considers the probabilistic nature of the lake ecosystem.